1999
DOI: 10.1111/j.1600-079x.1999.tb00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin‐induced inhibition of proliferation and G1/S cell cycle transition delay of human choriocarcinoma JAr cells: Possible involvement of MT2 (MEL1B) receptor

Abstract: Melatonin, the pineal neurohormone, is an evolutionarily conserved photoperiodic signaling molecule with diverse functions that include the entrainment of human circadian rhythms. Although evidence supporting a direct inhibitory action of melatonin on human cancer cell proliferation exists in the literature, the molecular and cellular signaling mechanisms involved are largely undefined. In our study, significant inhibition of human choriocarcinoma JAr cell proliferation at physiological and pharmacological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 33 publications
2
46
0
1
Order By: Relevance
“…It has been observed that melatonin levels are reduced in aged individuals that suffer from prostate cancer, and melatonin reduces proliferation of prostate cancer cells, suggesting a connection between the two events [43]. Similar results have been reported in human choriocarcinoma JAr cells, where melatonin inhibits proliferation and delays G1/S cell cycle transition [44]. Our data are consistent with above mentioned studies and imply that indole, similar to melatonin, is an anti-proliferative agent in the RPE cells.…”
Section: (B) (A)supporting
confidence: 82%
“…It has been observed that melatonin levels are reduced in aged individuals that suffer from prostate cancer, and melatonin reduces proliferation of prostate cancer cells, suggesting a connection between the two events [43]. Similar results have been reported in human choriocarcinoma JAr cells, where melatonin inhibits proliferation and delays G1/S cell cycle transition [44]. Our data are consistent with above mentioned studies and imply that indole, similar to melatonin, is an anti-proliferative agent in the RPE cells.…”
Section: (B) (A)supporting
confidence: 82%
“…Today, many of the oncostatic properties of melatonin have been fairly well described (Vijayalaxmi et al, 2002), and evidence from experimental studies strongly suggests a link between melatonin and tumour suppression (Schernhammer and Hankinson, 2003). In vitro studies, although not entirely consistent (Panzer et al, 1998), give support to a reduction in the growth of malignant cells of the breast (Hill and Blask, 1988;Cos et al, 1996Cos et al, , 1998Cos et al, , 2002Mediavilla et al, 1999) and other tumour sites (Sze et al, 1993;Ying et al, 1993;Petranka et al, 1999;Shiu et al, 1999;Kanishi et al, 2000) by both pharmacological and physiologic doses of melatonin. In rodent models, pinealectomy boosts tumour growth (Tamarkin et al, 1981), whereas exogenous melatonin administration exerts anti-initiating (Musatov et al, 1999) and oncostatic activity (Anisimov et al, 1997Cini et al, 1998;Mocchegiani et al, 1999) in various chemically induced cancers.…”
Section: Cancer-protective Effects Of Melatoninmentioning
confidence: 99%
“…In fact, to date, melatonin has been shown to be oncostatic for a variety of tumour cells in experimental carcinogenesis (Sze et al, 1993;Ying et al, 1993;Petranka et al, 1999;Shiu et al, 1999;Kanishi et al, 2000). Reports show that melatonin exhibits a growth-inhibitory effect on endometrial (Kanishi et al, 2000) and ovarian carcinoma cell lines (Petranka et al, 1999), Lewis lung carcinoma (Mocchegiani et al, 1999), prostate tumour cells (Laufer et al, 1999), and intestinal tumours (Anisimov et al, 1997(Anisimov et al, , 2000a, for example.…”
Section: Cancer-protective Effects Of Melatoninmentioning
confidence: 99%
“…30). Several in vitro studies have reported a reduction in the growth of malignant cells and/or tumors of the breast (31)(32)(33)(34)(35) prostate (36)(37)(38)(39)(40)(41), and other tumor sites (42)(43)(44)(45)(46) by both pharmacologic and physiologic doses of melatonin. In rodent models, pinealectomy has been found to enhance tumor growth (47), and exogenous melatonin administration has shown anti-initiating (48) and oncostatic (49)(50)(51)(52) activities in various chemically induced cancers as well as in virus-transmitted tumors in mice (53).…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%